1989
DOI: 10.1017/s0003356100004268
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in a tropical beef herd divergently selected for pregnancy rate

Abstract: Selection on the basis of estimated breeding value for cow fertility was successful in establishing two distinct lines of high (H) and low (L) fertility in a herd of Droughtmaster (Brahman x Shorthorn) cattle. The average difference in pregnancy rates over 3 years between the H and L line was 12% (P < 0-01) in the selected cows. In lactating cows this difference was 17% indicating that lactational anoestrus was an important component of the line difference in fertility. The total calf losses between confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…This behaviour predisposes young calves to wild dog attack -the age that also coincides with the time when most calves disappear and are recorded as 'unknown losses' in reproductive performance studies (e.g. Rankine and Donaldson 1968;Entwistle 1974;Holroyd 1977;Hetzel et al 1989;Burns et al 2010). In contrast, when cows and calves return to their herd, the behaviour of adult cattle to cooperatively protect calves, by mobbing against wild dogs if they threaten calves and forming crèches of up to 20 calves in the custody of two or three adult cattle, helps to deter wild dog attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour predisposes young calves to wild dog attack -the age that also coincides with the time when most calves disappear and are recorded as 'unknown losses' in reproductive performance studies (e.g. Rankine and Donaldson 1968;Entwistle 1974;Holroyd 1977;Hetzel et al 1989;Burns et al 2010). In contrast, when cows and calves return to their herd, the behaviour of adult cattle to cooperatively protect calves, by mobbing against wild dogs if they threaten calves and forming crèches of up to 20 calves in the custody of two or three adult cattle, helps to deter wild dog attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the losses of calves were found to occur within 14 days of birth and the largest proportion of loss was from unknown causes, where the calf carcass could not be found (Holroyd 1987a). In reviewing calf losses across northern Australia, Holroyd (1977) found that post-natal loss ranged from 2.3 to 31.4% and mostly occurred within 1 month of birth (see also Hetzel et al 1989; where 75% of calf losses were found to occur between the last trimester of pregnancy and 2 months of age), where the extensive nature of northern Australia's beef cattle industry and the lack of any intensive investigations were believed the cause why most calf losses were classed as 'unknown'. In reviewing calf losses between confirmed pregnancy and weaning over the last 25 years, Burns et al (2010) concluded that the large range of causes of peri-natal mortality rates remains poorly understood, with little progress made in determining causes of peri-and post-natal calf mortalities.…”
Section: Introductionmentioning
confidence: 99%
“…Although applying high selection intensities to lowly heritable traits can circumvent this problem, for example with beef cow reproduction (Hetzel et al 1989) or with litter size in sheep (Clarke 1972), another method of improving pregnancy rate in beef cattle could be to select on more highly heritable, correlated traits. An experiment of this type was set up by one of us (GLB) at Ruakura beginning with the mating/ calving years of 1981/1982.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a herd of 445 Droughtmaster cows, where those that lactated in the previous season had a 10% higher calf survival rate than those that did not lactate in the previous season (Hetzel et al, 1989). Given the low repeatability of foetal and calf mortality as reported in above studies, physical abnormalities, e.g.…”
Section: General Risk Factors Influencing Calf Survivalsupporting
confidence: 87%